Senolytic effects of quercetin in an in vitro model of pre-adipocytes and adipocytes induced senescence - Elena Zoico (Nature Portfolio, 2021)
Abstract The dysfunction of adipose tissue with aging and the accumulation of senescent cells has been implicated in the pathophysiology of chronic diseases. Recently interventions capable of reducing the burden of senescent cells and in particular the identification of a new class of drugs termed senolytics have been object of extensive investigation. We used an in vitro model of induced senescence by treating both pre-adipocytes as well as mature adipocytes with hydrogen peroxide (H2O2) at a sub-lethal concentration for 3 h for three consecutive days, and hereafter with 20 uM quercetin at a dose that in preliminary experiments resulted to be senolytic without cytotoxicity. H2O2 treated pre-adipocytes and adipocytes showed typical senescence-associated features including increased beta-galactosidase activity (SA-ß-gal) and p21, activation of ROS and increased expression of pro-inflammatory cytokines. The treatment with quercetin in senescent pre-adipocytes and adipocytes was associated to a significant decrease in the number of the SA-β-gal positive cells along with the suppression of ROS and of inflammatory cytokines. Besides, quercetin treatment decreased miR-155-5p expression in both models, with down-regulation of p65 and a trend toward an up-regulation of SIRT-1 in complete cell extracts. The senolytic compound quercetin could affect AT ageing by reducing senescence, induced in our in vitro model by oxidative stress. The downregulation of miRNA-155-5p, possibly through the modulation of NF-κB and SIRT-1, could have a key role in the effects of quercetin on both pre-adipocytes and adipocytes.